Addressing disparities in cancer clinical trials: a roadmap to more equitable accrual - Hoin, Jon A.; Carthon, Bradley C.; Brown, Shantoria J.; Durham, Lynn M.; Garrot, L. Crain; Ghamande, Sharad A.; Pippas, Andrew W.; Rivers, Brian M.; Snyder, Cindy T.; Gabram-Mendola, Sheryl Gordon Ann (Frontiers in Health Services, 2024)
The Georgia Center for Oncology Research and Education (Georgia CORE) and the Georgia Society of Clinical Oncology (GASCO) held a one-day summit exploring opportunities and evidence-based interventions to address disparities in cancer clinical trials. The purpose of the summit was to identify clear and concise recommendations aimed at decreasing clinical trial accrual disparities in Georgia for rural and minority populations. The summit included expert presentations, panel discussions with leaders from provider organizations throughout Georgia, and breakout sessions to allow participants to critically discuss the information presented. Over 120 participants attended the summit. Recognizing the need for evidence-based interventions to improve clinical trial accrual among rural Georgians and persons of color, summit participants identified four key areas of focus that included: improving clinical trial design, providing navigation for all, enhancing public education and awareness of cancer clinical trials, and identifying potential policy and other opportunities. A comprehensive list of takeaways and action plans was developed in the four key areas of focus with the expectation that implementation of the strategies that emerged from the summit will enhance cancer clinical trial accrual for all Georgians.